Effect of Work Environment and Organizational Culture on Employee Performance - Nurmaya Nurmaya; Muhammad Aqsa; Sapar Sapar (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to determine how much influence the work environment has on employee performance and organizational culture on employee performance. The object of this research is the nickel mining industry in Lutim Regency, associative research. The population is all employees at PT. Citra Lampia Mandiri (CLM) as many as 291 works of the cloud. The sample of this study used a sampling technique (method random sampling) or a simple method, namely by randomly using the Slovin formula as many as 74 employees. In this study, it was found that the work environment and organizational culture had a significant and positive influence on employee performance, either partially or simultaneously